COGNITIVE RESERVE ACROSS THE LIFE COURSE, APOE, AND LATE LIFE COGNITIVE TRAJECTORIES - Praetorius Björk, M (Innov Aging, 2018)
Few studies have examined the associations among cognitive reserve (CR), APOE, and late life cognition. In the present study we examined measures of CR across the lifespan (i.e. early life- midlife- and late life) in relation to level of cognitive performance and change in late life. We also examined whether and how these relationships are affected by different time metrics by comparing the effects of chronological age with time to death. The analyses were conducted in a sample of 501 initially non-demented individuals, aged 80 years and older, followed until death. Cognition was measured using the MMSE-test (Mini-Mental State Examination). The results indicate that the CR measures were related to level of performance as well as change in MMSE. Yet, CR at different stages of life influenced cognition variously depending on use of the age- or death-related model. In the age-based model, late life cognitive activity was related to level of MMSE while early life CR was associated with a terminal decline trajectory. Associations among late life cognitive functioning, cognitive reserve and APOE status were, however, mixed and less conclusive.